Cyclophilin D: Guardian or Executioner for Tumor Cells? - Zhang, Ling; Liu, Yi; Zhou, Rou; He, Baoyu; Wang, Wenjun; Zhang, Bin (Frontiers in Oncology, 2022)
Cyclophilin D (CypD) is a peptide-proline cis-trans isomerase (PPIase) distributed in the mitochondrial matrix. CypD regulates the opening of the mitochondrial permeability conversion pore (mPTP) and mitochondrial bioenergetics through PPIase activity or interaction with multiple binding partners in mitochondria. CypD initially attracted attention due to its regulation of mPTP overopening-mediated cell death. However, recent studies on the effects of CypD on tumors have shown conflicting results. Although CypD has been proven to promote the aerobic glycolysis in tumor cells, its regulation of malignant characteristics such as the survival, invasion and drug resistance of tumor cells remains controversial. Here, we elaborate the main biological functions of CypD and its relationships with tumor progression identified in recent years, focusing on the dual role of CypD in tumors.